Estudios de derecho sucesorio. Vol. II: Interpretación de testamentos. Por Juan B. Vallet de Goytisolo. Ed. Montecorvo. Madrid, 1981. 536 págs. - Martínez Val, José María (Estudios de Derecho, 1981)
Estudios de derecho sucesorio. Vol. II: Interpretación de testamentos. Por Juan B. Vallet de Goytisolo. Ed. Montecorvo. Madrid, 1981. 536 págs.